Total Synthesis of Marine-Derived Azole Resistant Antifungal Agent (–)-Melearoride A and Antibiotic (–)-PF1163B - Yasam, Bharath Kumar; Pabbaraja, Srihari (SynOpen, 2022)
A flexible stereoselective and convergent cum divergent approach to the synthesis of two 13-membered macrolides through a common skeleton present in their structure is described featuring two different routes, with good overall yield. The key synthetic reactions utilized include Keck allylation, Evans asymmetric methylation, Grubbs metathesis, and Julia–Kocienski olefination.
Keywords: macrolides; melearoride A; PF1163B; Julia–Kocienski olefination; ring-closing metathesis